1994
DOI: 10.1002/ep.670130115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adsorption characteristics for VOCs on activated carbon and oxidized activated carbon

Abstract: In this investigation, the selected activated carbon is treated in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Jointly with a slight increase of the adsorption capacity, it is possible to appreciate a tremendous increase of the mass transfer coefficient (K), doubling for the sample under the electric field. The amounts of MEK adsorbate at the equilibrium, normalized on weight, are comparable with the one found in the literature [49,50] if it is considered that the activated carbon amount in the present composite is approximately 44%. Fitted values of the Equation (7), relatively to the batch adsorption tests, are reported in Table 5.…”
Section: Enhanced Removal Of Vocsupporting
confidence: 87%
“…Jointly with a slight increase of the adsorption capacity, it is possible to appreciate a tremendous increase of the mass transfer coefficient (K), doubling for the sample under the electric field. The amounts of MEK adsorbate at the equilibrium, normalized on weight, are comparable with the one found in the literature [49,50] if it is considered that the activated carbon amount in the present composite is approximately 44%. Fitted values of the Equation (7), relatively to the batch adsorption tests, are reported in Table 5.…”
Section: Enhanced Removal Of Vocsupporting
confidence: 87%
“…This negative effect for gas phase adsorption of aromatics has been previously observed in the case of benzene [28,29]. In these studies [28] the authors concluded that the CO 2 -type groups are detrimental for the benzene adsorption whereas the CO-type groups favor it.…”
Section: Phenanthrene Adsorption Isotherm Analysismentioning
confidence: 76%
“…Although the research on the influence of surface chemistry in aromatic compounds in aqueous solution is very extensive [19,22,26], studies on gas phase are very scarce and limited to the adsorption of benzene vapors [28,29]. Consequently, the main objective of the present work is to explore the role of activated carbon surface chemistry in the adsorption of Phe vapors, one of the most abundant polyaromatic emitted in energy generation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Gasification occurs and CO 2 are produced when O 3 oxidizes the activated carbon surface. CO 2 exits the surface and creates new pores [36]. The consumption and the change of the carbon surface structure may influence the performance of VOC-ozone reaction and the regeneration of the media and hence activated carbon was not used in this study.…”
Section: Introductionmentioning
confidence: 99%